Tracing Tactile Patterns in Students with Vision Disability and Multiple Disabilities or Deafblindness - Παπαζαφείρη Μαρία; Αργυρόπουλος Βασίλειος (Education Sciences, 2024)
The present study aims to identify patterns of tactile exploratory behaviors applied by children with vision disability and multiple disabilities or deafblindness when interacting with a variety of objects. This identification process was based on the texture of the objects. Twenty-two students, 8-18 years old, who were enrolled in primary and secondary specialized educational programs, as well as in daycare centers, participated in this research. The students were invited to participate in two activities which involved small objects and cards and the authors asked the students to identify them through their texture. Relevant data was obtained through observation protocols and video recording. The results of the present study highlight the importance of tactile exploratory behavior patterns in understanding the development of the somatosensory system and learning behaviors of children with vision impairment and multiple disabilities or deafblindness. It is expected that the outcome of the study may contribute to the design of more targeted individualized programs for children with multiple disabilities and blindness in order to develop and excel their tactile skills and haptic apprehension. These programs may be developed within the field of special education, early intervention or/and in sensory integration programs.